STATEGI MENSTIMULUS EKONOMI KREATIF INDONESIA MELALUI DANA ALOKASI KHUSUS - Britany Alasen Sembiring (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2021)
In the past five years, President of Indonesia has intended to improve the Indonesian economya through the creative economy sector. The creative economy is parallel with Micro, Small and Medium Enterprises, where more than 90 percent Indonesian people put their livelihood. Therefore, the positive growth of the creative economy industry in Indonesia will faster stimulate local and national economic growth. Consequently, it is necessary to have the right policies, especially facilitation from the central government to local governments, which directly dealing with the Indonesian civil people. For example, through the Special Allocation Fund which properly encourage the creation of business leverage for MSMEs engaged in the creative economy industry. This study answers how central government transfer funds in the form of Special Allocation Funds can stimulate the creation of this acceleration of creative economic growth, especially in the pandemic era which bases its business on digital marketing. Using the simultaneous panel method of the local budget industrial sector (APBD sector) and central fund transfer (TKDD) for 34 provinces and other indicators such as labors, household consumption, the construction cost index, and investment in the form of PMTB from the 2014-2019 period, this study results in the significance of all these variables on the growth of the creative economic subsector. The output of this study shows that DAK has the most significant effect in increasing the economic growth of the creative economy in 34 provinces. In addition, investment and household consumption are the biggest levers in supporting the high growth of the creative economy. This is in accordance with the economic theory of the potter model and the neoclassical Solow growth model where investment and technology are important factors in the acceleration of economic growth. Given the condition of the Indonesian people, where most of which are MSMEs in the creative economy sector, investment through DAK to finance the technological transfer and research development is very significant. This was also confirmed through further research in this study in a qualitative method which conducted in-depth interviews with one of the Heads of Bakung Kidul Village, Cirebon. In the interview, there were several important inputs for the evaluation of transfer fund policies that support economic productivity in the creative economy sector, especially in the Tourism Village Area which was built 2 years ago. The results of this qualitative study were also enriched by interviews with DAK policy maker from the Directorate General Fiscal Balance, Ministry of Finance and MSME business actors who were also victims of the Covid-19 pandemic that hampered the Indonesian economy.